Stepping Into Vitality: How Brisk Walking Elevates Fitness Among the Elderly in Medan City - Ilham Rasyid Khani; Nurhayati Simatupang; Novita Sari Harahap; Yovhandra Ockta (Universitas Negeri Semarang, 2024)
The study conducted at the Guna Budi Bakti Foundation in Medan Labuhan focused on the impact of Brisk Walking Exercise on the fitness level of elderly individuals. With a sample size of 10 participants with an age range of 60 to 72 years. the research employed a pre-test and post-test experimental design over three weeks, with sessions held five times a week. Results indicated a significant improvement in fitness levels post-intervention, with participants transitioning from very poor to good fitness categories. Descriptive analyses and statistical tests confirmed the efficacy of the exercise program. The study underscores the importance of tailored exercise regimens in addressing age-related declines in fitness and promoting overall well-being among the elderly. Brisk walking, being accessible and adaptable, emerges as a practical aerobic activity for this demographic. The findings highlight the need for proactive measures to support healthy aging and emphasize the potential of structured exercise programs in enhancing the quality of life for elderly individuals. Continued efforts to promote physical activity among the elderly are crucial for sustaining their health and vitality in the aging process.